1989
DOI: 10.1159/000181101
|View full text |Cite
|
Sign up to set email alerts
|

Classical Pituitary Apoplexy Presentation and a Follow-Up of 13 Patients

Abstract: Thirteen patients who presented with signs and symptoms of pituitary disease gave a history of classical pituitary apoplexy. Six presented with acute symptoms and in 7 the history antedated the admission by a mean of 887 days (range 365–2,190 days). All patients had an enlarged eroded sella. CT scans revealed a bleed in the tumor in 11 (histologically confirmed in all 8 patients operated), evidence of residual tumor in 1 and an empty sella (ES) in 1 patient. Hypopituitarism was present in 9, 4 were endocrinolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This risk appears to be comparable in secreting and nonsecreting tumours and is lower in patients treated with radiotherapy [108]. Recurrent pituitary apoplexy is a rare event, although few cases have been reported [109]. It appears to be more common in patients managed conservatively than in those surgically treated [52].…”
Section: Prognosismentioning
confidence: 99%
“…This risk appears to be comparable in secreting and nonsecreting tumours and is lower in patients treated with radiotherapy [108]. Recurrent pituitary apoplexy is a rare event, although few cases have been reported [109]. It appears to be more common in patients managed conservatively than in those surgically treated [52].…”
Section: Prognosismentioning
confidence: 99%
“…[9] Most cases of pituitary apoplexy present in the fifth or sixth decade with a slight male preponderance ranging from1.1 to 2.25:1.0. [1013] In a recent retrospective analysis of 42 pituitary apoplexy patients from 1980 to 2007, the sex ratio was 3:1 with median age of the patients of 53.5 (range 21–85) years. [14] In the largest series from India studied at Vellore, the sex ratio was approximately 2:1 with mean age of presentation of 40.4 (range 18-65) years.…”
Section: Incidencementioning
confidence: 99%
“…[11145154] There are also studies showing higher prevalence among functioning tumors. [102555] Among the secreting tumors the highest prevalence was seen in prolactinomas. [141651] Study by Dubuisson et al .…”
Section: Predisposing Featuresmentioning
confidence: 99%
“…Recurrent apoplexy is well documented in patients who were managed non-surgically during their first apoplectic event 4;6;14;19;20 but it is rare after surgical treatment of the initial episode. Recurrent apoplexy following surgery was first reported by Ahmed et al 11 Other four cases reported since then are summarized in Table 1. With diligent, careful long-term follow-ups more cases should have been diagnosed.…”
Section: Discussionmentioning
confidence: 94%
“…2;4;14 Decreased perfusion pressure to the adenoma may even lead to spontaneous necrosis and disappearance of the tumour without significant symptoms. 11; 12 Alatakis has reported a patient with empty sella and pituitary apoplexy that occurred in the absence of tumour tissue. 12 Such cases suggest that a fraction of cases with empty sella may represent these burn-out tumour cases.…”
Section: Discussionmentioning
confidence: 99%